x+9-(3x/5)=(x/2)-3 this is my next question
Answers
Answered by
2
Hope this helpful to you....!
Attachments:
![](https://hi-static.z-dn.net/files/d19/d1e19b712f4469d736174db708ef980b.jpg)
Answered by
2
Answer: 120
Step-by-step explanation:
Let's solve your equation step-by-step.
x+9−
3x
5
=
x
2
−3
Step 1: Simplify both sides of the equation.
x+9−
3x
5
=
x
2
−3
x+9+
−3
5
x=
1
2
x+−3
(x+
−3
5
x)+(9)=
1
2
x−3(Combine Like Terms)
2
5
x+9=
1
2
x−3
2
5
x+9=
1
2
x−3
Step 2: Subtract 1/2x from both sides.
2
5
x+9−
1
2
x=
1
2
x−3−
1
2
x
−1
10
x+9=−3
Step 3: Subtract 9 from both sides.
−1
10
x+9−9=−3−9
−1
10
x=−12
Step 4: Multiply both sides by 10/(-1).
(
10
−1
)*(
−1
10
x)=(
10
−1
)*(−12)
x=120
Answer:
x=120
hope it helps!! have a nice day,thank u!!!!!!!!!!!!!!!!
Similar questions